KADAR DEBU UDARA PADA BAGIAN PRODUKSI UD.MANDIRI DI DESA TELUK KECAMATAN PURWOKERTO SELATAN KABUPATEN BANYUMAS TAHUN 2018 - Nisa Adelia; Tri Marthy Mulyasari (Poltekkes Kemenkes Semarang, 2019)
Air quality is influenced by many things, one of which is pollutants. Wood industry is one of the industries that produce pollutants in the form of dust. Dust-exposed workers are at risk for health and disease complaints, both infectious and non-infectious diseases (cancer). The purpose of this research is to measure the dust, temperature, humidity, wind speed and wind direction in production section of UD. Mandiri In Teluk Village of South Purwokerto Sub District Banyumas District. The type of research used is descriptive. The data were collected through interviews, questionnaires, and documentation. Data is presented in the form of tables, drawings and narratives. The research results total dust content in production UD.Mandiri got the result of average 2,12 mg/m3 unders the standard Permenkes No. 70 of 2016 at work place the highest dust content is allowed is 10 mg / m3. Measurement of air temperature got the result of average 33,2oC exceeds standard (24oC-26oC). Measurement of air humidity got the result of average 58,8% under standard (65%-95%), Measurement wind speed got the result of average 0,16 m/s standard wind speed (0,15-0,25 m/s), result of wind direction determination more dominant towards the Northeast. The conclusion is total dust content in production UD.Mandiri exceeds the standard Permenkes No. 70 of 2016, air temperature exceeds standard, air humidity under standard, standard wind speed, dominant wind to the Northeast. Efforts that can be made to control the dust levels in the production section are by vacuum cleaner, the owner provides personal protective equipment in accordance with the hazards present in the production section